Monetary and Fiscal Policy Options for Dealing with External Shocks : Insights from the GIMF for Colombia - Flores, Enrique; Clements, Benedict; Leigh, Daniel (Washington, D.C. : International Monetary Fund, 2009)
This paper utilizes an open-economy New Keynesian overlapping generations model, the Global Integrated Monetary and Fiscal Model (GIMF), to assess the macroeconomic effects of external shocks and the impact of various monetary and fiscal policy responses. The simulations assess the effect of shocks to trade, world income, and risk premia for public debt. The results suggest that under Colombia's inflation targeting regime, which incorporates exchange rate flexibility and a highly responsive monetary policy, the economy is well poised to adjust to different external shocks. They also suggest that the potential role of fiscal policy in responding to shocks depends critically on financing conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet